Патентно-информационное обеспечение инновационной деятельности в Новосибирской области (Библиосфера)
Patent and information provision of innovation activity in Novosibirsk region is considered. At the embodiment on the example of SPSL work on the Federal target program «Development of nanotechnology infrastructures in the Russian Federation». The set of organizations working in the field of nanotechnology is proposed. A detailed list of sources to meet the information needs of organizations participating in nanotechnology network in Novosibirsk region is proposed. Opportunities for access to information resources are presented.